Assessment of Particulate Matters Especially PM2.5 and PM10 Concentration During and Before Lockdown in the Various Metropolitan Cities of India - SINGH, Gourav Kumar; SINGH, Shivom; RAI, Swapnil; JADON, Nimisha (Journal of Environmental Management and Tourism, 2022)
This study was carried out to evaluate the concentration of particulate matter i.e. PM 2.5 & PM 10 in the selected metropolitan area (Mumbai, Delhi, Kolkata & Bengaluru). Data used and analysed in this research was taken from the official website of CPCB (Central Pollution Control Board). Analysis is done before and during the lockdown period. For the current analysis, data from the chosen parameters (Particulate Matter with a diameter equal to or less than 10 microns (PM 10 ) and particulate matter with a diameter equal or less than 2.5 microns (PM 2.5 ) are gathered and analysed from the source i.e. CPCP. Site wise, histogram analysis was also performed. The PM concentration is found to be the highest in Delhi, among all locations. During the study period, a clear association between PM 10 and PM 2.5 was observed at all the sites. A great change was observed in the values of Particulate Matter before and after the lockout cycles. In metro cities, values higher than PM 10 were found to be PM 2.5 , except for Bangalore, where values lower than PM 10 were found to be PM 2.5 . During the lockdown, Bengaluru was least polluted while Delhi was the most polluted city among all these metropolitan cities. During the analysis it was observed that the level of Particulate Matter (PM) got reduced as all kind of anthropogenic activities were stopped. Vehicular activities and other construction work were also stopped so it helped to reduce the PM from the surroundings. COVID-19 brought a meaningful drive to combat all kind of air related pollution and it is observed during this research.